Satisfacción laboral de los asalariados en Espa\~na - Paz Rico Belda (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2012)
– The aim of this paper is to identify the explanatory factors of job satisfaction of employees in Spain, with special emphasis on gender and nationality differences. For doing that, an ordered multiple answer model will be estimated, using data from the Living Standards Quality in the Job corresponding to years 2006 to 2010. The results show that, after controlling by personal and employment characteristics of employees, there is a positive differential in job satisfaction level in favour of women. However, there is none of evidence that there is a nationality difference in job satisfaction. Moreover, the job stability, employees involvement in their companies, a good business climate and conciliation between career and familiar life affect positively to job satisfaction, but the mismatch in training and in working hours influence negatively to satisfaction of employees.
Keywords: C25; J28; 330; job satisfaction; gender differences; ordered multiple answer models; immigration; marginal effects